A higher degree of resilience: Using psychometric testing to reveal the benefits of university internship placements. (July 2020) - Goodenough, Anne E; Roberts, Hazel; Biggs, David M; Derounian, James G; Hart, Adam G; Lynch, Kenny
Resilience is a multifaceted concept but, in the context of learning, it can best be thought of as an individual's capacity to create and maximise opportunities as well as responding positively to setbacks and challenges. Developing students' resilience is becoming increasingly important. Research has shown resilience links to attainment, retention, engagement and employability. However, very little work has examined what aspects of curricula enhance resilience and the particular role of active learning frameworks in achieving this. In this study, we analyse the effects of optional real-world internship placements on eight measures of resilience. Psychometric testing was conducted twice per student – at the start of their second academic year and again at the end. Students choosing an internship had significantly higher challenge orientation and adaptability scores than other students in the same cohort. Adaptability of both interns and non-interns improved over the academic year, but improvement was significantly higher for interns. Scores for optimism, purposeful direction and ingenuity significantly increased between start-of-year and end-of-year tests for interns versus a decline for non-interns. We conclude that facilitating student engagement with real-world issues and challenges through supported internships within an active learning framework is an important mechanism for increasing students' resilience.